FAKTOR YANG MEMPENGARUHI KECURANGAN LAPORAN KEUANGAN DENGAN PERSPEKTIF FRAUD TRIANGLE (Studi Empiris pada Perusahaan Property, Real Estate dan Building Construction) - Yohannes Suharsana; Chatarina Prisiena (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2019)
This research is to analyzed influence of variable pressure which proxied by financial stability,external pressure, and financial target, and then variable opportunity which proxied by nature ofindustry, ineffective monitoring, and variable razionalization which proxied by auditor change withfraudulent financial statement which measured with fraud score model (F-Score).The sample used in this research are 26 companies of property, real estate, and buildingconstruction sector that listed in Indonesian Stock Exchange on the period 2011 to 2015. The type datathat used are secondary data, from the annual reports of companies sample.The result of this statistical research showed that the variables of financial stability thatmeasured with change in total asset ratio, financial target variable that measured with ROA (return onassets), and nature of industry variable that measured with the change in receivables ratio has positiveinfluence on the fraudulent financial statement. The research does not prove that external pressurevariable which measured with leverage ratio, ineffective monitoring variable which measured with thepercentage of board members who are outside members, and change auditor which measure withdummy variable has an influence on the fraudulent financial statement.